Peran Otoritas Jasa Keuangan Terhadap Pengaturan Dan Pengawasan Pada Perbankan Syariah Indonesia - Ngafifatul Waro; Nely Arifah Tulistyawati; Laila Hanifah; Endang Kartini Panggiarti (Journal of Creative Student Research, 2023)
The Financial Services Authority (OJK) as a regulator of the money management sector, especially the financial sector, must adequately equip its capabilities to properly implement and support financial management sector activities. economic growth. OJK has a position in managing Islamic banks. The description of Islamic commercial banks is very important because they are only marginal in accelerating the development of the financial economy, especially micro, small and medium enterprises (MSMEs). The Financial Authority carries out the functions, duties, authority to regulate and control activities in the financial sector in an integrated, independent and responsible manner, particularly in the world of banking. The problems of this research are: First, how independent is the Financial Services Authority in regulating and supervising banks? Second, what is the role of the Financial Services Authority in regulating and supervising banks? Third, what is the role of the Financial Services Authority in consumer protection and consumer investigations? The type of research method is normative law and the type of research is descriptive. In conclusion: First, other parties do not interfere with the independence of OJK in its regulation and are found to be inseparable from government interference. Such deals can lead to government intervention. Second, the role of OJK in regulating and supervising banks related to the regulation and supervision of micro stability is very broad. Third, OJK's role in consumer protection is to inform and educate the public about the good quality of the financial sector, its services and products. Stop if it can harm consumers. It is recommended: First, in addition to regulating the independence of the OJK, there must also be freedom from state intervention, so that the government cannot intervene. Second, that the OJK really places the interests of the national economy and not the interests of entrepreneurs as the center of its regulatory task. Third, clarify the provisions that make it easier for the OJK to handle consumer complaints, so that there is no prejudice as if the OJK is providing financial support to consumers.